Advances in CRT - Buckley, Rita (MD Conference Express, 2012)
It has been suggested that the future of cardiac resynchronization therapy (CRT) will be based on indications for treatment, patient selection, imaging guidance to enhance efficacy, and the advantages and disadvantages of various lead and implant placement methods. This article discusses key findings from recent clinical trials with CRT and summarized critical issues for its future.